Aspidistra yizhouensis sp. nov. (Asparagaceae) from limestone areas in Guangxi, China - Pan, Bo; Lu, Zhao-Cin; Ma, Hu-Sheng; Lin, Chun-Rui (Phytotaxa, 2016)
A new species Aspidistra yizhouensis (Asparagaceae) is described and illustrated from limestone areas in central Guangxi, China. It is similar to Aspidistra fungilliformis, but has perianth urceolate, lobes yellow adaxially, pistil obconical, stigma upper surface purplish red and with 3 yellow, radial, bifurcate lines.